Interpretation Of Al-Qur'an In The Disruption Era: Reversing Roles Of Ulum Al-Qur’an - Rusydi AM; Mhd. Idris (Jurnal Ulunnuha, 2020)
This study aims to find out the important rules in interpreting the Qur'an. The Qur'an is the Muslim holy book, but the Qur'anic guide is not only for Muslims but for all humanity without exception. This is the meaning of hudan linnas. To carry out this strategic function, we must interpret the Qur'an with many conditions, such as Arabic, knowledge of the Qur'an (ulum al-qur'an), hadith, ushul fiqh, science and so on. These are the fundamental and essential foundations of the interpretation of the Qur'an. Today, interpreters sometimes do not obey these basics and lead people to the wrong path. For that reason, there are three things that intersect each other in the understanding and interpretation of the Qur'an by a mufassir, namely: mastering the rules of the Arabic language, understanding that a verse interprets other verses and masters the principle of munasabah.